KONSEP QIWĀMAH DALAM YURISPRUDENSI ISLAM PERSPEKTIF KEADILAN GENDER - Faizah, Nur (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2018)
This article explains the concept of leadership in the family (qiwāmah) gender justice perspective. The focus of the study on the interpretation of Surat an-Nisā '[4] verse 34 which becomes the theological and socio-cultural foundation of society. The letter interprets that the husband is superior to the wife, so marriage relations tend to be hierarchical (the husband becomes the head of the family, while the wife has the subordinate status). This lame husband and wife relationship makes the wife vulnerable to violence. The author considers that this verse must be reinterpreted from the point of view of gender justice given the sociological shift. This study led the writer to the conclusion that the concept of qiwāmah in Islamic jurisprudence is open and dialogic with the times. The concept of qiwāmah now must be interpreted based on human values rather than gender, so that women as wives not only serve their husbands, but partners and partners who are both subjects and objects. The relationship between them is in the form of symbiosis of mutualism (mutual benefit), not only in the family but also for the community and the State. There is no difference between the two, except in matters of devotion to God. [Artikel ini menjelaskan konsep kepemimpinan dalam rumah tangga (qiwāmah) perspektif keadilan gender. Fokus kajian pada penafsiran Surat an-Nisā’ [4] Ayat 34 yang menjadi landasan teologis dan sosio-kultural masyarakat. Surat tersebut menafsirkan bahwa suami lebih unggul daripada istri, sehingga hubungan perkawinan cenderung hierarkis (suami menjadi kepala keluarga, sementara istri berstatus subordinat terhadapnya). Relasi suami istri yang timpang ini membuat istri rentan terhadap kekerasan. Penulis memandang bahwa ayat ini harus ditafsir ulang dari sudut pandang keadilan gender mengingat adanya pergeseran sosiologis. Kajian ini mengantarkan penulis pada kesimpulan bahwa konsep qiwāmah dalam yurisprudensi Islam bersifat terbuka dan dialogis dengan perkembangan zaman. Konsep qiwāmah sekarang harus dimaknai berdasarkan nilai-nilai kemanusiaan bukan jenis kelamin, sehingga perempuan sebagai istri bukan hanya melayani suaminya, melainkan patner dan mitra yang sama-sama menjadi subyek sekaligus obyek. Relasi keduanya berupa simbiosis mutualisme (saling menguntungkan), tidak hanya dalam keluarga tetapi juga untuk masyarakat dan Negara. Tidak ada perbedaan di antara keduanya, kecuali dalam hal ketakwaan kepada Tuhan.]